Intellectual capital and national innovation systems performance - Lu W.-M.; Kweh Q.L.; Huang C.-L. (Elsevier B.V., 2023)
Innovation is a key resource for the well-being of national economies and international competitive advantages. First, this study develops a network data envelopment analysis (DEA) production process to evaluate the R&D efficiency and economic efficiency of the national innovation system (NIS) in 30 countries. Our findings show that the R&D efficiencies of the NIS are better than the economic efficiencies. Second, this study examines the effect of intellectual capital (IC) on the NIS performance through truncated regression. Our findings indicate that IC does play an important role in affecting the NIS performance. Finally, this study presents a managerial decision-making matrix and makes suggestions through a performance improvement strategy map to help government and managers improve the NIS performance. ©2014 Elsevier Ltd. All rights reserved.